Mechanical properties of concrete to concrete interfaces under uniaxial and shear forces - Kabay, Nihat; Kizilkanat, Ahmet Beser (PAMUKKALE UNIV, 2018)
This research aims to evaluate the bond strength between normal strength substrate concrete and different types of high strength overlay concretes. In order to obtain different characteristics in the overlay concrete, silica fume and steel fibers were used. The slant shear and bi-surface shear tests were conducted to quantify the effect of different high strength concrete compositions on the bond strength. The mechanical properties of overlay/substrate concrete composites were also analysed on cylindrical samples under uniaxial compression load. The results indicate that the strength of overlay plays an important role on the bond mechanism. The bond strength is found to be dependent on the test mechanism. The test results showed that the bond strength was about 6-12 times higher in slant shear test compared to the bi-surface shear test. The application of parallel model approach on the overlay/substrate concrete composites was found to be quite satisfactory to predict the elastic modulus of the composite.
Keywords: Bond strength; Slant shear test; Bi-surface shear test; SUBSTRATE; Engineering